UJI EFEKTIFITAS PUPUK DAUN TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS TANAMAN KUBIS ( Brassica oleracea L. ) - Nasikhun Nasikhun; Teguh Supriyadi; MAHANANTO MAHANANTO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2011)
This study aimed to investigate the influence Veriety on growth and yield of cabbage, known effect of foliar fertilizer also result growth and cabbage plants as well as the combination and the type of fertilizer veriety also leaf growth and leaf also result cabbage plants as well as the interaction of Veriety and type of fertilizer also leaf growth and yield of cabbage plant. This research was conducted in the village of Wonosobo regency Kalikajar Wonosari District central of Java.Time implementation began at September 7, 2009 by December 7, 2009. Topogarvi sloping andosol soil types, elevation 1100 feet from surface water by usingÂ SplitÂ plot prepared with the basic pattern planing randomized complete block (Block). Factors such research are: 1) Variety (V) consists of levels, ie: V1 = Grand 11, V2 = grand sarira, V3 = green Corronet. 2) Fertilizer leaves (D) consists of three levels namely: D1 = Powergrow, D2 = Bisagrow, D3= Supergrow. All treatments performed three times, the results showed the following results: (1) The treatment of varieties (V) showed significant effect on fresh weight crop cultivation, has a very significant effect on the diameter of the crop, significantly affect the crop per plot weight, significantly affected the fresh weight crown and significant effect on dry weight crown. (2). Whereas foliar fertilizer treatments (D) showed significantly affect the number of leaves, has a very significant effect on fresh weight crop cultivation, has a very significant effect on the diameter of the crop and significant effect on dry weight crown. (3). As for treatment combination between the varieties with a foliar fertilizer (VxD) showed highly significant effect on the diameter of the crop, the highest value was obtained on treatment combination (V1D2) is 21.63cm, whereas the lowest value was obtained on treatment combination (V3D3) is 15.13cm. (4). The highest result it was achieved in treatment combination grand 11 variety of cabbage with powergrow leaves fertilizer (V1D1) was 26,73kg per plot (55,69tons/Ha) and the lowest result it was achieved in treatment combination Green Corronet variety with supergro leaves fertilizer (V3D3) is 20,50kg per plot (42,71tons/Ha).